THE EFFECT OF COOPERATIVE MODEL TYPE OF NUMBERED HEADS TOGETHER (NHT) ON STUDENTâS ACHIEVEMENT ON STATIC FLUID AT YEAR XI SEMESTER II SMA NEGERI 11 MEDAN A.Y. 2015/2016 - Tambunan, Dewi Sartika; Motlan, Motlan (JURNAL IKATAN ALUMNI FISIKA UNIVERSITAS NEGERI MEDAN, 2017)
This research is aimed to know and describetthe studentâs outcomes using Cooperative learning model ofNumbered Heads Together (NHT) type in theÂ  static fluidtopic grade XI Science in SMA Negeri 11 Medan A.Y. 2015/2016.This research employed a quasi experimental with the population were grade XI- Science in Negeri 11 Medan, the population consists of five classes. The sample consists of two classes while the technique used by cluster random sampling, class XI-science2 using cooperative learning model of Numbered Heads Together type and class XI Sciences1 using conventional learning. Research instrumentsÂ  multiple choice tests for pre-test and post-test 20 questions. ForÂ  the hypothesis test used different test, after the prerequisite test is done, the test for normality and homogeneity test.From the research the pretest average value of experiment classÂ  39.42 and standard deviation 12.93 and average value of post test in experiment class 78 and standard deviation 10.92, while the control classÂ  obtained average value of pretest 36.71 and standard deviation 10.49 and average value of postest 65.14 andÂ  standard deviation 10.81. Both ofÂ  class showed normal distribution and variance both of class are homogeneous . The result t test tcount = 4.96 andttable = 1.669, so tcount > ttable (4.96> 1.669) the result showed that the implementation of cooperative learning model of Numbered Heads Together (NHT) typehave significantlyÂ  to the learning outcomes of students in fluid static topic grade XI-Science SMA Negeri 11 Medan A.Y. 2015/2016. Result of student activity also showed student in Cooperative Learning Model class has good activeness. Thus, the activity has effect toward the students outcome.